2001
DOI: 10.1007/s100380170031
|View full text |Cite
|
Sign up to set email alerts
|

An association of 5,10-methylenetetrahydrofolate reductase (MTHFR) gene polymorphism and common carotid atherosclerosis

Abstract: Plasma homocysteine (Hcy) concentration has been shown to be influenced by a mutation in the gene coding methylenetetrahydrofolate reductase (MTHFR). Although plasma Hcy is related to atherosclerotic disorders, conflicting results have been reported about the association between MTHFR gene polymorphism and sclerotic lesions of the common carotid arteries. The effect of agegene interaction on carotid arterial remodeling was investigated in elderly subjects with several risk factors for atherosclerosis. We evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 27 publications
1
19
1
Order By: Relevance
“…There are studies that describe a positive relation, but measurement of folate was not done in all of them [13,14,28]. In a recent meta-analysis a positive association of coronary disease with MTHFR 677TT mutation has been described when folate status was low or normal, but not when it was high [10].…”
Section: Discussionmentioning
confidence: 93%
“…There are studies that describe a positive relation, but measurement of folate was not done in all of them [13,14,28]. In a recent meta-analysis a positive association of coronary disease with MTHFR 677TT mutation has been described when folate status was low or normal, but not when it was high [10].…”
Section: Discussionmentioning
confidence: 93%
“…Several other studies also confirmed that MTHFR C677T is a key genetic determinant of lipid profiles. For example, evidence that the MTHFR gene polymorphism is an important independent contributor to TC and HDL-C was found by Kawamoto et al [19], and Pitsavos et al reported that TC and TG are statistically different across MTHFR genotypes [20]. Another functional polymorphism in the MTR gene is A2756G, located at position 919 of the protein and resulting in a substitution of glycine for aspartic acid [21].…”
Section: Discussionmentioning
confidence: 99%
“…41,42) However, different results for the association between MTHFR C677T genotype and atherosclerosis have been reported. Woodside 43) showed that arterial PWV is not associated with MTHFR genotype in a healthy young population, while Kawamoto 44) proved that MTHFR C677T genotype was associated with carotid atherosclerosis in an elderly Japanese population. Our study demonstrates that increased Hcy levels, rather than MTHFR C677T genotype, are associated with the development of baPWV in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%